Field comparison of sterol-biosynthesis-inhibiting fungicides used alone and in combination with protectant fungicides for apple scab control - Warner, J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Several sterol-biosynthesis-inhibiting (SBI) fungicides were tested alone and in combination with a broad-spectrum protectant material in field trials for control of Venturia inaequalis. When used in a 10-day spray schedule, SBI fungicides, whether used alone or in a mixture, provided improved scab control as compared to the protectant material used alone. With bitertanol, diniconazole, and penconazole, the mixture also provided better scab control than when the SBI fungicide was used alone. However, with flusilazole and myclobutanil, no improvement in disease control occurred with the mixture as compared to the SBI fungicide alone. Fruit russeting was observed after a post-bloom application of hexaconazole and growth-regulating effects on the foliage were observed following cyproconazole and hexaconazole use. The use of SBI fungicides in mixtures to avoid or delay the development of fungus resistance is discussed.